Effect of surcharge on stabilized peat soil from Sarawak - Julian, Gabriel Bain (Universiti Malaysia Sarawak, UNIMAS, 2010)
Peat soil has always been a problem in Malaysia where peat is found to be abundantly present. Currently, a lot of studies have been conducted to improve the condition of the soft and troublesome peat soil in Malaysia. Present study is to analyse the effect of subjecting surcharge loading of 1 kg on stabilized peat soil, in the prospect of increasing its compressive strength after the peat has been stabilized using cheap and accessible stabilizing materials. Depending highly on the pozzolanic reaction between calcium oxide and fly ash alone, the author aims to harness the use of coal - by product which is abundantly found in Sarawak. However, as the results have shown, the use of calcium oxide and fly ash as stabilization materials and subjecting surcharge load is insufficient and ineffective in improving and increasing the compressive strength of the peat soil in Sarawak.